Sosialisasi Program Pengorganisasian Masyarakat di Sekolah Melalui PIK-R Dalam Mencegah Pergaulan Bebas di Kalangan Siswa dan Siswi SMP Al-Azhar Medan - Rahim Tarigan, Abdul; Arya Pratama, Adriansyah; Hariyanti, Atika Ayu; Sheillawany, Anggun; Hagareninsa Br Bangun, Clarissa Adisty; Syafira, Dita; Herdini Saragih, Devi; Safitri, Novia; Mardiah, Nurul Ainun; Wahyuni, Rista (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
The Youth Information and Counseling Center (PIK-R) was established as a platform for the Preparation for Family Life Program for Adolescents (PKBR). Various statistical data, such as WHO estimates on adolescent risky sexual behavior and the results of health surveys in Indonesia, indicate a high prevalence of unprotected sex and out-of-wedlock pregnancies. This research was conducted at SMP Al-Azhar Medan with the aim of providing health education on the Community Organization Program in Schools Through PIK-R to prevent free mixing among adolescents. The research employed a quantitative approach with an experimental pre-test and post-test design. The participants were 28 eighth-grade students, with the majority being females (57.1%). Before the education session, a pre-test was conducted, revealing that 92.9% of students had good knowledge. Following the education session, the post-test showed a significant improvement, with 96.4% of students now having good knowledge. Statistical analysis indicated a non-significant difference between pre-test and post-test scores. The average knowledge score increased from 1.04 to 1.07. However, a p-value > 0.05 suggests that this difference is not statistically significant. In the effort to prevent free mixing among adolescents, health education through the Community Organization Program in Schools via PIK-R can positively contribute to increasing students' knowledge.